Enhanced physical therapy for arm function after stroke: a one year follow up study. Issue 7 (July 1994) - Sunderland, A; Fletcher, D; Bradley, L; Tinson, D; Hewer, R L; Wade, D T
Abstract : Ninety seven patients with stroke who had participated in a randomised trial of conventional physical therapy nu an enhanced therapy for arm function were followed up at one year. Despite the emphasis of the enhanced therapy approach on continued use of the arm in everyday life, the advantage seen for some patients with enhanced therapy at six months after stroke had diminished to a non-significant trend by one year. This was due to some late improvement in the conventional therapy group whereas the enhanced therapy group remained static or fell back slightly. It is recommended that trials should be conducted comparing very intensive therapy for the arm with controls without treatment. This would provide a model of the effects of therapy on intrinsic neural recovery that would be relevant to all areas of neurological rehabilitation.